Analisa Sistem Proteksi Petir Pada Jaringan Transmisi 70-30 Kv Gi Dolopo - Golang - Fatkur rohman rohman; Trisna Wati (Institut Teknologi Adhi Tama Surabaya, 2023)
On the 70-30 kV Dolopo-Golang transmission network, the disturbance data due to lightning surges is quite high, reaching 642/year. Based on the IEEE standard used in this study, the data is quite large in terms of disturbances from lightning strikes. Therefore, the potential disturbance caused by lightning is in dire need of attention. Calculations were carried out using the Anderson method as an IEEE standard. The results of the analysis and calculations carried out using the MATLAB m-file indicated that the SFFOR values in the transmission network for the 150 Kv GI from Ngimbang to Mliwang conductors in 2018-2020 for the number of plates 7-9 were 10,264, 50,975, and 50,975 disturbances/100km/year. These values were still relatively high compared to the IEEE standard of 0.05 disturbances/100km/year. Consequently, the protection system of GI 150 KvNgimbang-Mliwang must be evaluated for the sake of isolator plate improvement. The values of SFFOR and BFOR must be reduced because the greater the number of isolator discs, the greater the optimal lightning impulse voltage capability that the isolator disc can withstand. The number of discs 7 to 9 could only be applied to GI 70 kV Dolopo-Golang 1 and GI 70 kV Dolopo-Golang 2 because two of the flashover values from the three available years (2018-2020) had values less than or equal to 0.05